ANALYSIS ENGLISH SPEAKING DIFFICULTY LEVEL BY GRADE VII STUDENTS OF SMPI DARUDDA’WAH - Nanda, Rio (Cahaya Ilmu Bangsa Institute, 2024)
This study aims to analyze the level of difficulty speaking in English among class VII students at SMPI Darudda'wah. Difficulty speaking English is one of the challenges that students often face, especially in the early stages of learning. This research uses a descriptive method by collecting data through questionnaires and giving written tests, which are given to class VII students. The data obtained was analyzed to identify factors that influence speaking difficulties, such as limited vocabulary, mastery of grammar, lack of self-confidence, and other external factors. The results showed that the majority of students had difficulty constructing appropriate sentences, pronouncing words correctly, and communicating spontaneously in English. It is hoped that these findings will provide insight into English language teaching at SMPI Darudda'wah, as well as provide recommendations for improving students' speaking skills through a more effective and comprehensive approach.